Celastrol Efficacy by Oral Administration in the Adjuvant-Induced Arthritis Model - Cascão, Rita; Vidal, Bruno; Carvalho, Tânia; Lopes, Inês Pascoal; Romão, Vasco C.; Goncalves, João; Moita, Luis Ferreira; Fonseca, João Eurico (Frontiers in Medicine, 2020)
Background: We demonstrated that celastrol has significant anti-inflammatory and bone protective effects when administered via intraperitoneal route. For further preclinical evaluation an effective oral administration of celastrol is crucial. Here we aimed to study the therapeutic dose range for its oral administration. Methods: Celastrol (1-25µg/g/day, N=5/group) was administrated orally to female AIA rats after 8 days of disease induction for a period of 14-days. A group of healthy (N=8) and arthritic (N=15) gender and age-matched Wistar rats were used as controls. During the treatment period the inflammatory score, ankle perimeter and body weight were measured. At the end of the treatment animals were sacrificed, blood was collected for clinical pathology, necropsy was performed with collection of internal organs for histopathological analysis, and paw samples were used for disease scoring. Results: Doses higher than 2.5µg/g/day of celastrol reduced the inflammatory score and ankle swelling, preserved joint structure, halted bone destruction, and diminished the number of synovial CD68+ macrophages. Bone resorption and turnover were also reduced at 5 and 7.5µg/g/day doses. However, the dose of 7.5µg/g/day was associated with thymic and liver lesions and higher doses showed severe toxicity. Conclusion: Oral administration of celastrol above 2.5µg/g/day ameliorates arthritis. This data supports and gives relevant information for the development of a preclinical test of celastrol in the setting of a chronic model of arthritis since rheumatoid arthritis is a long-term disease.